Easy-cone magnetic structure in (Cr0.9B0.1)Te - He, Yangkun; Fecher, Gerhard H.; Kroder, Johannes; Borrmann, Horst; Wang, Xiao; Zhang, Lunyong; Kuo, Chang-Yang; Liu, Cheng-En; Chen, Chien-Te; Chen, Kai; Choueikani, Fadi; Ohresser, Philippe; et al. (Applied Physics Letters, 2020)
Although stoichiometric CrTe is difficult to synthesize because of the appearance of Cr vacancies, ferromagnetic Cr1-x Te compounds have attracted increasing attention. This work investigates single crystalline (Cr0.9 B0.1)Te with the Cr vacancies filled by B to stabilize the hexagonal crystal structure and shift the Fermi energy. The structural and magnetic properties have been characterized by experimental measurements and ab initio calculations. A collinear spin structure with an easy axis along c is observed at high temperature, whereas the magnetic moments localized at the Cr atoms gradually tilt away from the c-axis below 140 K. A maximum tilt angle of 30 ° is observed at a temperature of 2 K.
CRIS-Team Scopus Importer:2022-04-14